2009
DOI: 10.1063/1.3117515
|View full text |Cite
|
Sign up to set email alerts
|

Radiation damage to amorphous carbon thin films irradiated by multiple 46.9 nm laser shots below the single-shot damage threshold

Abstract: High-surface-quality amorphous carbon (a-C) optical coatings with a thickness of 45 nm, deposited by magnetron sputtering on a silicon substrate, were irradiated by the focused beam of capillary-discharge Ne-like Ar XUV laser (CDL = capillary-discharge laser; XUV = extreme ultraviolet, i.e., wavelengths below 100 nm). The laser wavelength and pulse duration were 46.9 nm and 1.7 ns, respectively. The laser beam was focused onto the sample surface by a spherical Sc/Si multilayer mirror with a total reflectivity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 30 publications
0
8
0
Order By: Relevance
“…Such lasers can enable fundamental studies and be utilized for applications such as nanomachining 14,15 and the development of nanoprobes. [16][17][18] We present the results of experiments undertaken with an argon capillary discharge laser, producing nanosecond pulses at a wavelength of 46.9 nm, focused onto thin parylene-N targets. This type of plastic contains equal proportions of hydrogen and carbon, which simplifies radiation-hydrodynamic simulations.…”
Section: Introductionmentioning
confidence: 99%
“…Such lasers can enable fundamental studies and be utilized for applications such as nanomachining 14,15 and the development of nanoprobes. [16][17][18] We present the results of experiments undertaken with an argon capillary discharge laser, producing nanosecond pulses at a wavelength of 46.9 nm, focused onto thin parylene-N targets. This type of plastic contains equal proportions of hydrogen and carbon, which simplifies radiation-hydrodynamic simulations.…”
Section: Introductionmentioning
confidence: 99%
“…A simultaneously non-thermal desorption of the carbon coating and an extrusion of the Si substrate could be supposed processes. This conclusion is reasonable due to the findings of [15] where a ablation caused by multiple laser shots below the single shot damage threshold could be observed and [13] with the findings of extrusions for a-C under illumination with fluences below 0.2 J/cm 2 at a wavelength of 32.5 nm at FLASH. Also the radiation in the present experiment with a wavelength of 21 nm has a transmission through the carbon coating to the silicon substrate of 50 % under an angel of α=80° [4].…”
Section: Discussionmentioning
confidence: 49%
“…In later experiments the damage threshold of a 40 nm thick a-C coated mirror was determined to 43.7 ± 13 mJ/cm 2 for a FLASH wavelength of 7 nm (177 eV) [14]. In further experiments to analyze the behavior of mirrors under multiple laser shots an a-C coated Si substrate was irradiated with 46.9 nm laser pulses [15]. As light source a Ne-like Ar 8+ XUV laser with a pulse duration of 1.7 ns was applied.…”
Section: Introductionmentioning
confidence: 99%
“…Irradiation of amorphous carbon with multiple XUV laser pulses at a uence below the single-shot damage threshold still showed an erosion of the material. 93 This is an unexpected behavior because above the single-shot threshold the authors rst observed expansion, then ablation and then a-C lm delamination from the silicon substrate. Henceforth, the character of the process changed dramatically in the vicinity of the single-shot damage threshold, i.e., erosion turns into expansion.…”
Section: Xuv/sxr Laser In the Progress Of Laser Microanalysismentioning
confidence: 97%